1993
DOI: 10.1029/93jd01840
|View full text |Cite
|
Sign up to set email alerts
|

Mean winds and tides in the upper middle atmosphere at Urbana (40°N, 88°W) during 1991–1992

Abstract: A summary of the first 18 months of continuous wind observations using the Urbana medium frequency (MF) radar is presented. Emphasis is placed on height-time contours of monthly mean winds and on amplitudes and phases of 24 hour and 12 hour tides. Results are compared with data from other midlatitude stations and models. Below 85 kin, monthly mean winds are shown to agree closely with the zonal mean, geostrophic wind model CIRA86. Significant dis•ancies above 85 km have been noted in comparisons between CIRA86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 14 publications
(4 reference statements)
2
26
0
Order By: Relevance
“…The climatology of mesospheric winds observed at Urbana has been previously derived using the spaced antenna full correlation analysis technique [Franke and Thorsen, 1993]. The SA-FCA climatology, consisting of monthly means obtained by averaging 5-min velocity estimates, is compared here with the time domain interferometry technique.…”
Section: Mean Windsmentioning
confidence: 99%
See 1 more Smart Citation
“…The climatology of mesospheric winds observed at Urbana has been previously derived using the spaced antenna full correlation analysis technique [Franke and Thorsen, 1993]. The SA-FCA climatology, consisting of monthly means obtained by averaging 5-min velocity estimates, is compared here with the time domain interferometry technique.…”
Section: Mean Windsmentioning
confidence: 99%
“…Over the past few decades, long-term climatologies of the mesospheric circulation generated by medium frequency (MF) radars employing the spaced antenna full correlation analysis (SA-FCA) technique have played a fundamental role in strengthening our understanding of mesospheric dynamics [ Gregory and Manson, 1975;Manson et al, 1985Manson et al, , 1991Franke and Thorsen, 1993]. At the same time, the effects of external noise, radar antenna geometry, and signal processing (e.g., finite record length, sampling interval, filtering) on the SA-FCA technique have been investigated [Golley and Rossiter, 1970 …”
Section: Introductionmentioning
confidence: 99%
“…The operation of the MF radar to obtain atmospheric winds is discussed by Franke and Thorsen [1993]. For this paper the 12 individual month composite days are used which are derived from a seven year climatology.…”
Section: Experimental Instrumentation and Techniquementioning
confidence: 99%
“…) and appear to propagate westwards following the motion of the Sun (e.g., Chapman and Lindzen, 1970). Remote sensing investigations of the MLT region using ground-based radar (e.g., Avery et al, 1989;Vincent et al, 1989;Franke and Thorsen, 1993;Thayaparan, 1997) and spaceborne optical sensors on the Upper Atmospheric Research Satellite (UARS) (e.g., Hays et al, 1994;Burrage et al, 1995;Shepherd et al, 1995;McLandress et al, 1996;Geller et al, 1997) have provided a wealth of data on the local time and global scale effects of solar tides on the wind field. Together with recent model developments such as the Global Scale Wave Model (GSWM) Hagan, 1996), these studies have revealed a complex, yet understandable, mean global variation Copy right c The Society of Geomagnetism and Earth, Planetary and Space Sciences (SGEPSS); The Seismological Society of Japan; The Volcanological Society of Japan; The Geodetic Society of Japan; The Japanese Society for Planetary Sciences.…”
Section: Introductionmentioning
confidence: 99%